Addressing oral health equity through community service-learning and person-centered care in Ontario: patient and provider perspectives - Abbas Jessani; Giuliana Gadoni Giovanni Borges; Jacqueline Torti; Zachary Hollingham; Trixie Patricia Vos; Natasha Roden; Sarah McLean (PLoS ONE, 2025)
This study aimed to investigate the influence of the Community Service-Learning (CSL) program at Schulich Dentistry on the experiences and perceptions of patients and healthcare providers (HCP) at the Oxford County Community Health Centre (OCCHC) in Ontario, Canada. The CSL program aimed to address the oral health needs of equity-deserving populations and provide dental learners with experiential, community-based training. A qualitative research methodology using a Community-Engaged Research (CEnR) framework was employed. Data was collected through one-on-one interviews with 21 patients and six HCPs at the OCCHC. Inductive thematic analysis was conducted to identify key themes. As a result, five main themes were identified, with overlap between patients and HCPs. Two major themes emerged from the interviews with patients (1) challenges and barriers to dental care and (2) enhanced access to dental care through the CSL program; highlighting stigma and discrimination due to public dental insurances and low socioeconomic status. From the HCPs’ perspectives, (3) person-centred care was the main identified theme, emphasizing the importance of understanding patients’ individualized circumstances and social determinants of health when providing dental care. Additionally, common themes between patients and HCPs were also identified as (4) supportive environment and (5) patient empowerment and self-confidence. In conclusion, the CSL program addressed the oral health needs of equity-deserving patients by improving patient access to dental care while increasing patients’ self-esteem and confidence through a person-centred care approach. These findings highlight the importance of community-integrated models of dental care in addressing oral health inequities and training future dental professionals.